Entrepreneurs’ Perceived Roles in Phnom Penh: A Multidimensional Assessment of Passion, Innovation, Risk-Taking, and Proactiveness - Bunheng Ban; Pio Sario T (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to assess entrepreneurs’ perceived roles in Phnom Penh, Cambodia, focusing on four cognitive dimensions: passion, innovation, risk-taking, and proactiveness, and to examine differences in these perceptions across selected demographic and enterprise characteristics. Methodology: A quantitative descriptive-comparative research design was employed. Data were collected from 226 entrepreneurs using a structured Likert-scale questionnaire. Statistical tools included mean, standard deviation, Pearson correlation, and one-way ANOVA. Data analysis was conducted using IBM SPSS Statistics, supported by a relevant literature review and secondary data sources. Main Findings: The findings reveal a high overall level of perceived entrepreneurial roles. Proactiveness recorded the highest mean, followed by passion and innovation, while risk-taking was moderate. No significant differences were found across age and firm size, whereas the sector showed significant differences in passion and risk-taking. Novelty/Originality of this study: This study provides a multidimensional assessment of entrepreneurial role perceptions in Cambodia, emphasizing cognitive dimensions rather than performance outcomes. It offers new empirical evidence from Phnom Penh and contributes to the limited literature on entrepreneurial cognition in developing economies, supporting more context-specific research and policy development.